Disease-modifying anti-rheumatic drugs improve the cardiovascular profile in patients with rheumatoid arthritis - Giachi, Andrea; Cugno, Massimo; Gualtierotti, Roberta (Frontiers in Cardiovascular Medicine, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting about 0.5-1% of the adult population and manifesting as persistent synovitis, systemic inflammation and production of autoantibodies. Patients affected by RA not only experience chronic disease progression, but are also burdened by a 1.5-fold increased cardiovascular (CV) risk, which is comparable to the risk experienced by patients with type 2 diabetes mellitus. RA patients also have a higher incidence and prevalence of coronary artery disease (CAD). Although RA patients frequently present traditional CV risk factors such as insulin resistance and active smoking, previous studies have clarified the pivotal role of chronic inflammation - driven by proinflammatory cytokines such as interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-alpha) - in accelerating the process of atherosclerosis and impairing the coagulation system. Over the last years, a number of studies have shown that disease-modifying anti-rheumatic drugs (DMARDs) reducing the inflammatory state in general improve the CV risk, however some drugs may carry some apparent negative effects. Thus, RA is a model of disease in which targeting inflammation may counteract the progression of atherosclerosis and reduce CV risk. Clinical and experimental evidence indicates that the management of RA patients should be tailored based on the positive and negative effects of DMARDs on CV risk together with the individual traditional CV risk profile. The identification of genetic, biochemical and clinical biomarkers, predictive of evolution and response to treatment, will be the next challenge for a precision approach to reduce the burden of the disease.